Construction of a hydrazine oxidoreductase gene recombinant bacterium for effective N2H4 removal from wastewater. (December 2021) - Liu, Yangyang; Lu, Yongsheng; Yang, Xingxing; Xu, Yunfeng; Chen, Xueping; Qian, Guangren; Liu, Qiang
Abstract: Anaerobic ammonium oxidation (anammox) receives considerable attentions from researchers because it could achieve biological denitrification from wastewater with low carbon resource input. During anammox, hydrazine oxidoreductase (HZO) plays a critical role in the biological conversion of ammonium (NH4 + ) to dinitrogen gas. In this study, we constructed a HZO gene recombinant bacterium by genetic process technology with the aim to effectively remove N2 H4 in anammox process. The result indicates about 80% N2 H4 -N could be removed by the obtained HZO gene recombinant bacterium under the optimum condition (an initial N2 H4 -N concentration of 5 mg/L and a bacterial dosage of 20 mL). More importantly, the high N2 H4 -N removal efficiency (about 70%) could be maintained when HZO gene recombinant bacterium spread to the sixth generation. The recombinant protein of HZO gene recombinant bacterium could be successfully expressed and show a stable activity to N2 H4 removal under low intensity wastewater, suggesting the removal of N2 H4 was attributed to the successful expression of HZO enzyme of anammox bacterium in E. Coli .